DNA programming in drug discovery and drug development - Ravi kumar maddali; Naga kishore R (International Journal of Pharmacy and Analytical Research, 2023)
Important traits that biological cells have that make them appealing for many applications are energy efficiency, self-reproduction, and small size. Examples include the incorporation of intelligence into smart materials, sensing, and nanoscale manufacturing. Simple "genetic circuits" that are encoded in DNA and carry out their functions in the cellular environment have been developed over the past 15 years. A gene circuit uses biological interactions to provide computation, similar to an electronic circuit. Simulators that replicate cell colonies running microbial programmes have been developed at the protein and language levels.